Prophylactic effects of intrathecal Meperidine and intravenous Ondansetron on shivering in patients undergoing lower extremity orthopedic surgery under spinal anesthesia - Mohammadreza Safavi; Azim Honarmand; Maryam Negahban; Mohammadali Attari (Wolters Kluwer Medknow Publications, 2014)
Objective: Intraoperative hypothermia is a common problem with anesthesia. Spinal anesthesia, the same as general anesthesia, affects the process of temperature regulation. The aim of this study was to compare the prophylactic effect of intravenous (IV) ondansetron with intrathecal (IT) meperidine on prevention of shivering during spinal anesthesia in patients underwent orthopedic surgery of the lower limb. Methods: In this study, 120 patients with American Society of Anesthesiologists physical status I to II, between the ages 16 and 65 were randomized into three groups. Group O and Group M were given IV ondansetron 8 mg and IT meperidine 0.2 mg/kg, before spinal anesthesia, respectively. Group C received IV saline 0.9%. The core and ambient temperatures, the incidence and intensity of shivering, blood pressure, heart rate, and maximum level of sensory block were recorded. Findings: Shivering was observed in 15%, 2.5%, and 37.5% of patients in Groups O, M, and C, respectively. There was a significant difference between Group O and M compared to Group C (P = 0.023 for Group O vs. Group C, P < 0.001 for Group M vs. Group C, P = 0.049 for Group M vs. Group O). Shivering incidence and intensity in Group M was significantly lower than Group O (P = 0.049 and P = 0.047, respectively). Twenty-two patients required additional IV meperidine among which 15 patients were from Group C (37.5%), six patients from Group O (15%) and one patient from Group M (2.5%). Conclusion: We concluded that IT meperidine and IV ondansetron comparably can decrease intensity and incidence of shivering compared to control group as well as decreasing the requirement to additional doses of meperidine for shivering the control without any hemodynamic side effect.